2013
DOI: 10.1111/1756-185x.12191
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac manifestations other than valvulopathy in antiphospholipid syndrome: long-time echocardiography follow-up study

Abstract: Pulmonary hypertension is the most prevalent non-valvular cardiac manifestation in APS, with an evolution associated with thromboembolic disease, while left myocardial disease and intracardiac thrombi would be rare manifestations in APS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 28 publications
0
11
0
3
Order By: Relevance
“…A case report from Snipelisky et al shows a patient with antiphospholipid syndrome who had three myocardial infarctions over a period of two weeks, who was treated with primary percutaneous coronary intervention with stent implantation in the fi rst myocardial infarction (5). Th e most frequent nonvalvular cardiac manifestation in patients with antiphospholipid syndrome is pulmonary hypertension (6). According to a follow-up echocardiography study by Kampolis et al in patients with antiphospholipid syndrome and systemic lupus erythematosus, disease duration is an independent factor for the progression of valvular disease, and anticoagulants could not stop the advancement of the valvular dis-FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
“…A case report from Snipelisky et al shows a patient with antiphospholipid syndrome who had three myocardial infarctions over a period of two weeks, who was treated with primary percutaneous coronary intervention with stent implantation in the fi rst myocardial infarction (5). Th e most frequent nonvalvular cardiac manifestation in patients with antiphospholipid syndrome is pulmonary hypertension (6). According to a follow-up echocardiography study by Kampolis et al in patients with antiphospholipid syndrome and systemic lupus erythematosus, disease duration is an independent factor for the progression of valvular disease, and anticoagulants could not stop the advancement of the valvular dis-FIGURE 2.…”
Section: Discussionmentioning
confidence: 99%
“…50 Since then, several authors have confirmed the association of APS and PH; the only exception is a single report by Pardos-Gea et al refuting an increased prevalence of PH in APS. 51 aPL-positive patients might present PH following a PE, might develop PAH associated with systemic sclerosis (SSc), SLE, or other connective tissue disease (CTD), or might present pulmonary venous hypertension associated with Libman-Sacks endocarditis. 48 If PH in the context of APS might be due to several causes, it is undeniable that the most common etiology acknowledges a thrombotic mechanism, as reckoned in 1984 when Anderson and Ali illustrated the case of a 26 year-old male with a positive LA who developed PH following recurrent episodes of DVT and PE despite prolonged anticoagulant therapy.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…In a recent study including 53 patients with primary and secondary (SLE) APS PAH, TTE demonstrated that PAH was the most frequent nonvalve cardiac disease, with a rate of 11.3%. 94 Angio-CT scan is the imaging tool of choice for the evaluation of PE and PE-related PAH in the general population, as in APS as well. 95…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%